1998
DOI: 10.1063/1.122274
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-induced three-dimensional bright and long-lasting phosphorescence inside calcium aluminosilicate glasses doped with rare earth ions

Abstract: Analysis of energy transfer processes in Yb3+-Tb3+ co-doped, low-silica calcium aluminosilicate glasses J. Appl. Phys. 110, 083108 (2011); 10.1063/1.3653272Long-lasting phosphorescence in Sn 2+ -Cu 2+ codoped silicate glass and its high-pressure treatment effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(69 citation statements)
references
References 9 publications
0
69
0
Order By: Relevance
“…In the past several years, many research efforts have been devoted to the field of 3D microscopic modifications to transparent materials by using femtosecond lasers. Promising applications have been demonstrated for the formation of 3D optical memory 6,[14][15][16] and multicolor images, 17) and the fabrication of optical waveguides, 5,18) couplers 7,19) and photonic crystals. 20) In the latest an applied research, Hosono et al fabricated fine-pitched micrograting structures in an amorphous SiO 2 thin film with a single femtosecond laser pulse, 21) and demonstrated that simultaneous formation of a color center and waveguide with femtosecond laser-induced microgratings produced an oscillating DFB color laser inside a LiF crystal by the femtosecond laser pulses interference technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, many research efforts have been devoted to the field of 3D microscopic modifications to transparent materials by using femtosecond lasers. Promising applications have been demonstrated for the formation of 3D optical memory 6,[14][15][16] and multicolor images, 17) and the fabrication of optical waveguides, 5,18) couplers 7,19) and photonic crystals. 20) In the latest an applied research, Hosono et al fabricated fine-pitched micrograting structures in an amorphous SiO 2 thin film with a single femtosecond laser pulse, 21) and demonstrated that simultaneous formation of a color center and waveguide with femtosecond laser-induced microgratings produced an oscillating DFB color laser inside a LiF crystal by the femtosecond laser pulses interference technique.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers try to install certain defects into crystalline and glass materials to control the decay time of long-lasting phosphorescence. Numerous practical materials have been developed, which an emission is strong enough to be observed by naked eyes for a time period exceeding 8 h. So far, long-lasting phosphorescence phenomena have been observed in rareearth ions doped polycrystalline [7,8] and glasses which were prepared under strong reduction environment [9 -11] or were treated by an infrared femtosecond laser [12,13]. In this paper we report that a long-lasting phosphorescence phenomenon was observed in a Sn 2þ -Cu 2þ co-doped silicate glass without any special treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Defects controlling and mechanical properties improvement in alloys can be realized by adjusting the parameters during the semi-solid metal (SSM) forming processes [7]. External electromagnetic fields induced defects-related photostimulated luminescence and long-lasting phosphorescence glasses have potential applications for X-ray sensors, optical memory and optical displays [8][9][10][11]. In the past, the defects are mostly induced by external electromagnetic fields, e.g.…”
Section: Introductionmentioning
confidence: 99%